Ageing in place in an inclusive community / Noorlailahusna Mohd Yusof and Suziana Mat Yasin - Mohd Yusof, Noorlailahusna; Mat Yasin, Suziana (2021)
A sustainable society is all about promoting peaceful communities, ensuring access to justice for all, and establishing competent, responsible, and inclusive institutions at all levels. Essentially, the development process can enhance the quality of life among the members of society. However, with the unprecedented rise in the number of older people worldwide, it is more vital than ever to address the issues and concerns of serving their needs. And one of the issues related to older people is related to their preference for aging in place. Older people who do not know what will happen in the future will most likely choose to remain in their current homes and city (Abramsson & Hagberg, 2020). Even older people might not age well in homes that are inaccessible or unaffordable. They may benefit from aging in an inclusive society where social networks, known services, and high perceived comfort and safety levels are prevalent. Therefore, this paper aims to identify the characteristics of an inclusive society for older people to age in place.